IMPLEMENTATION OF PEACE-LOVING AND UNITY CHARACTERISTICS IN DOLOKSANGGUL KB STIKES DORMITORY - Pardomuan Simanulang; Jesika Yohana Sitorus; Jeremia Togatorop (SEAN Institute, 2023)
Instilling character education from an early age is crucial in preventing violence and riots among students. Parents must make efforts to instill peace-loving values, ensuring that good character traits are ingrained in their children. Love for peace is demonstrated through attitudes, words, and actions that promote happiness, safety, and comfort in others. In line with the third precept of Pancasila, which emphasizes